Mahardika Dance Creation Process - I Wayan Sutirtha; Hendra Santosa; Tudhy Putri Apyutea Kandiraras (Jurnal Seni Tari, 2023)
This paper aims to reveal a creative process of the Mahardika dance creation conducted in 2006. This disclosure is important to see how the concept of traditional dance development still maintains the Balinese identity. The Mahardika dance, a new creation form of Balinese dance, comes from the creative process between I Wayan Sutirtha as the dance choreographer and I Nyoman Windha as the musical composer of the dance accompaniment. Mahardika means freedom or release from worldly ties, which refers to the Sutasoma figure as the central character in the Mahardika dance. It is adapted from the main theme of the Bali Arts Festival, namely Swabawaning Idep, meaning the radiance of nobility. The process of creating dance refers to the theory of Alma M. Hawkins in the book Creating Through Dance, including exploration, improvisation, and formation. The Mahardika dance consists of four parts. The first part describes the atmosphere of meditation with a silent atmosphere, the second part depicts the meeting of the Sutasoma and Dewi Candrawati with a happy and romantic atmosphere, the third part portrays the war of the Sutasoma and Prabu Purusadha with a tense atmosphere, and the fourth part represents the consciousness of Prabu Purusada and Sutasoma sitting on a lotus flower with a serene atmosphere. In addition, the costumes are adjusted to the characters. Certainly, it does not interfere with the dancer's movements but helps and opens aesthetic spaces in the choreography of the Mahardika dance creation.